Inequities in pediatric abusive head trauma according to neighborhood social and material deprivation: a population-level study in British Columbia, Canada - Beaulieu, Emilie (Child maltreatment, 2020)
Objectives:To explore the relationship between neighborhood social and material deprivation and the rates of abusive head trauma (AHT), and whether it differs according to sex, and following the implementation of the Period of PURPLE Crying (PURPLE) program.Method:A cross-sectional study design was applied to data from children 0 to 24 months old with a confirmed AHT diagnosis between 2005 and 2017 in British Columbia. Dissemination area-based social and material deprivation scores were assigned to residential areas, where AHT cases were recorded. Poisson regression models tested the relationship between deprivation scores and AHT rates, adding sex and pre-post program implementation as interaction terms.Results:With each increase in material and social deprivation quintiles, AHT rates increased by 42% (95% CI [1.18, 1.72]) and 25% (95% CI [1.06, 1.51]), respectively, following a social gradient. AHT rate disparities between neighborhoods did not change following the PURPLE program implementation.Conclusions:This study stresses the need to provide additional AHT prevention services proportionately to the levels of neighborhood disadvantage, in addition to universal AHT programs, to successfully protect all children.